(untitled) (Social Science Review, 2024)
This study delves into the analysis of communal violence in Bangladesh, focusing on the 2012 violent attack on the Buddhist community in Ramu, Cox’s Bazar. It examines the extent to which the attack affected the social cohesion of the local Muslim and Buddhist communities and evaluates the efficacy of post-violence responses for strengthening social cohesion and building resilience. We applied a mixed-method approach by using descriptive statistics from a survey of 300 local people and qualitative data from Focus Group Discussions and Key Informant Interviews. Based on an analytical framework of communal violence and resilience-building, this paper argues that communal violence is an ideologically motivated phenomenon that endangers inter-community relations, which cannot be fully recouped as various inadequacies undermine post-violence initiatives. The violent attack on the Buddhist community in Ramu was, in this vein, instigated by rumour and misinformation, igniting communal sentiment using a questionable Facebook post/tagging, intentionally used to mobilise locals and outsiders. Besides immediate consequences such as the destruction of property and the desecration of ancient religious places, it damaged inter-community relations by creating trauma, mistrust, and fear, which ruptured social interaction. The authorities could not prevent the attack due to their inability to understand the gravity of the issue. The immediate recovery support was quick and sufficient. However, it remained limited to reinstating the structures destroyed by the attack. Steps undertaken by different authorities for resilience-building were restricted. Therefore, grassroots people remain unattached in social cohesion building and coexist in subtle discomfort, if not anxiety. Social Science Review, Vol. 40(2), December 2023 Page: 143-170